The growing importance of ecological factors to employees in the transport and logistics sector - Lizbetinova, Lenka; Lejsková, Pavla; Nedeliakova, Eva; Caha, Zdenek; Hitka, Milos (Taylor & Francis Ltd., 2021)
The motivational preferences of employees can be statistically determined, but not lifted out of context in terms of the field they work in. The transport and logistics sector is undergoing a significant transformation, characterised by new technological solutions in everyday practice. It is a sector subject to a high number of legislative, economic, social, technological and environmental changes. Such changes have a secondary influence on the expectations, values and therefore preferences and job satisfaction of employees. The objective of this contribution is to identify the development of the motivational preferences of employees in the transport and logistics sector over time. These changes are monitored within the context of key changes and the strategic direction of the sector. The achievement of the objective is based on the partial results of research conducted by means of a questionnaire survey (n = 3,543) on motivational preferences and job satisfaction within the field. The ANOVA test and Tukey's HSD test were used for the verification of the hypotheses. The results show that employee preferences are changing significantly, with the most significant increase being identified in the case of social factors (environmental approach, corporate vision and regional development), reflecting current green innovation trends in the sector. Also, employees perceive education and professional growth, self-realisation, competencies, corporate prestige, physical and mental demands, content and type of work, working hours and environment and such feedback on results as increasingly important. On the other hand, there is declining emphasis on basic salary.
Rostoucí význam ekologických faktorů pro zaměstnance v sektoru dopravy a logistiky
Keywords: transport and logistics; motivation; preferences of employees; ecological approach; digitalisation; doprava a logistika; motivace; preference zaměstnanců; ekologický přístup; digitalizace